2021
DOI: 10.3390/ma14164403
|View full text |Cite
|
Sign up to set email alerts
|

PCL-Coated Multi-Substituted Calcium Phosphate Bone Scaffolds with Enhanced Properties

Abstract: Ionic substitutions within the hydroxyapatite lattice are a widely used approach to mimic the chemical composition of the bone mineral. In this work, Sr-substituted and Mg- and Sr-co-substituted calcium phosphate (CaP) scaffolds, with various levels of strontium and magnesium substitution, were prepared using the hydrothermal method at 200 °C. Calcium carbonate skeletons of cuttlefish bone, ammonium dihydrogenphosphate (NH4H2PO4), strontium nitrate (Sr(NO3)2), and magnesium perchlorate (Mg(ClO4)2) were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 41 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The investigation of the combination of PCL with bioceramic particles such as CaPs is a related topic of current research, and intensive efforts have been made to elaborate the most ideal composite for biomedical applications. In tissue engineering, PCL-CaP composites can be used as scaffolds [164][165][166][167][168][169] as well as coatings [37,[170][171][172][173][174][175][176][177][178].…”
Section: Polycaprolactone (Pcl) Composites (Petroleum-based)mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of the combination of PCL with bioceramic particles such as CaPs is a related topic of current research, and intensive efforts have been made to elaborate the most ideal composite for biomedical applications. In tissue engineering, PCL-CaP composites can be used as scaffolds [164][165][166][167][168][169] as well as coatings [37,[170][171][172][173][174][175][176][177][178].…”
Section: Polycaprolactone (Pcl) Composites (Petroleum-based)mentioning
confidence: 99%
“…Xu et al [165] fabricated 3D artificial polycaprolactone (PCL)-HAp bones by the fused deposition modeling technique. Bauer et al [166] recently prepared PCL-coated multi-substituted calcium phosphate bone scaffolds with improved properties. They used ionic doping within the hydroxyapatite phase to imitate the chemical composition of the bone mineral.…”
Section: Polycaprolactone (Pcl) Composites (Petroleum-based)mentioning
confidence: 99%
“…In our previous studies, individual (Mg 2+ and Sr 2+ ) and dual-ion substitutions (Mg 2+ and Sr 2+ ) into the HAp crystal structure have been studied [26,27]. Mechanical (compression) tests were performed on uncoated and PCL-coated Mg and Mg-Sr substituted calcium-phosphate structures.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive strengths of the uncoated scaffolds ranged between 0.20 and 0.35 MPa, while the coated scaffolds showed values higher than 1.1 MPa. In vitro cell culture studies showed that scaffolds are nontoxic and provide an adequate 3D support for cell attachment and proliferation [26].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the incorporation of bioactive glass (BG) increased the bioactivity, and the ion-doping changed the physical-chemical composition of the biomaterial in a way that enhanced its biological effect. The CaP or bioactive glass containing PCL composites are widely used as scaffold materials in bone tissue engineering [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]; however, in our work, we have focused on developing biodegradable and highly biocompatible thin layers onto the surfaces of metallic implants. The biominerals added nanocrystalline calcium phosphate powder had been embedded into a biopolymer matrix to enhance the adherence and control of the bioresorbility of the coating.…”
Section: Introductionmentioning
confidence: 99%